Analisis Penerapan Model Pembelajaran Kontekstual Berbasis Meaningful Learning di Sekolah Dasar - Kadek Selda Brilianda Mandalika (Jurnal DinamikA, 2025)
This study aims to reveal and describe the implementation of the contextual learning model based on meaningful learning in primary schools as an effort to create relevant, active, and meaningful learning experiences. Using a descriptive qualitative approach, data were obtained through observation, interviews, and documentation of teaching practices that integrate students’ real-life contexts with academic concepts. The findings reveal that this model enhances not only students’ engagement and learning motivation but also their conceptual understanding and critical thinking abilities. Teachers act as facilitators who bridge concrete experiences with abstract knowledge, forming a continuum of meaning that deepens the learning process. This research contributes theoretically to the development of meaningful learning strategies in primary education while offering practical insights for educators in designing contextual, meaning-oriented, and sustainable learning environments.